Pesantren Sebagai Potensi Pengembangan Dakwah Islam - Hariya Toni (Jurnal Dakwah dan Komunikasi, 2016)
Boarding School is an institution that transforms education and exemplary values every second and minute and every hour of the clerics to his students. Educational boarding school students aim to forge themselves into an independent person and to develop a spirit of togetherness, which includes the attitude of mutual assistance, solidarity and brotherhood among the students. In terms of individual character development, schools teach thrift and simple life away from the consumptive nature. Thus, Boarding School as an educational institution owned by the community is really potential for the Establishing of Human Resources (HR), potential for the creation of intelligence and well-being of the nation. Not a bit of Da’wah that could be done through schools, good Da’wah that convey the teachings of Islam, as well as preaching about the life and development of the Ummah.